ANALISIS YURIDIS PERAN PEMERINTAH ACEH DALAM PELATIHAN TENAGA KERJA - Muhibuddin M; Nasrianti N (LPPM Universitas Malikussaleh, 2021)
Manpower development contained in the 1945 Constitution Article 27 paragraph (2), that every citizen has the right to work and a decent living for humanity. The Aceh Government implements Article 174 paragraph (5), and Article 175 paragraph (4) of Law Number 11 Year 2006 concerning the Government of Aceh, therefore issued Qanun Number 7 of 2014 concerning Manpower and the Regulation of the Governor of Aceh Number 112 of 2016 concerning Position, Organizational Structure, Duties, Functions and Work Procedures of the Office of Manpower and Mobility of the Aceh Population. The method used in this study is a normative juridical research method that is qualitative in nature, namely research methods that refer to legal norms contained in legislation. In this study the use is referring to legal sources, namely research that refers to legal norms contained in legal instruments. Conclusion, provisions of Article 175 of Law No. 11 of 2006 concerning the Government of Aceh, that every worker has the same right to get decent work in Aceh. So the role of the Aceh Government in improving the direction of life of its people is very important in employment for the implementation of social justice in labor life.